Estimating the needs for artesunate-based combination therapy for malaria case-management in Africa. - Snow, R; Eckert, E; Teklehaimanot, A (2003)
Because of inadequacies in national health information systems, the volumes of drugs required to support an effective policy transition toward artesunate-based combination therapy (ACT) are unknown for most African countries. A series of national surveys and population projections have been used to estimate the age-structured fever burden among 41 malaria endemic countries in Africa. Under present fever-management guidelines, commodity costs and internationally agreed coverage targets, the financial resources to meet the needs of ACT in most African countries are huge. Between US$1.6 billion and US$3.4 billion per annum must be found to give Africa the chance to consider a drug policy based on ACT. Substantial reductions in these costs would be achieved through more effective targeting of resources--only 20% of drugs would be required to manage fevers among the most at-risk pediatric patient populations. Better diagnostics would also be an important consideration for a new ACT policy in Africa.